On the Diophantine System x^2 - Dy^2 = 1-D and x=2z^2-1 - Le, Maohua (MATHEMATICA SCANDINAVICA, 2004)
Let D be a positive integer such that D-1 is an odd prime power. In this paper we give an elementary method to find all positive integer solutions (x, y, z) of the system of equations x^2-Dy^2=1-D and x=2z^2-1. As a consequence, we determine all solutions of the equations for D=6 and 8.